Sistem Automatic Exhaust Fan Menggunakan Sensor DHT11 Dan Sensor MQ-135 Untuk Mendeteksi Kualitas Udara Ruang Industri - Agung, Dwi Julivan; Firmansah, Arif (Journal Electric Field, 2025)
Air quality has become a concern recently. Poor industrial indoor air quality has an impact on the number of deaths according to World Health Organization data. To reduce indoor air pollution, an autonomous exhaust fan system using DHT11 and MQ-135 sensors is presented. The design and experiment methods were carried out with a test variation of 1-10 minutes. The test results of each sensor showed that the average temperature was 26.8°C and humidity was 72%. Meanwhile, the MQ-135 sensor showed fluctuations in sensor resistance that were inversely proportional to the gas concentration (ppm). In the MQ-135 sensor test, a reference gas concentration value of 423.85 ppm was used to determine the accuracy of the sensor results. The detected gas concentration ranged from 402.9-469.8 ppm close to the reference value. The exhaust fan design system is recommended for office and industrial spaces to produce better indoor air quality.